Původ kreativní ekonomiky včetně demonstraci vlivu na hospodářský rozvoj - Kloudová, Jitka; Ondřej Chwaszcz (Vysoké učení technické v Brně, Fakulta podnikatelská, 2013)
Purpose of the article: This study presents the comprehensive theoretical framework of a new growth theory called “creative economy”. Recently, more and more of awareness is given to the creativity. Actually, the European Union nominates the year of 2009 as a year of creativity and innovation. On the other hand there is still not any unification concept of the creativity. Methodology/methods: That is why there is a need to formulate new paradigm in a form of creative economy, so that we would be able to understand the role of creativity in economic and social development. To construct the basic pillars of creative economy, this study used selected milestones from previous growth theories and as well is inspired by the period of modern economic growth that began with the emergence of an Industrial Revolution. Scientific aim: This theory defines a new emerging paradigm based on the presenting points. In the final section, theoretical conclusions of this work are documented by outputs obtained thanks to using a New creative index. This index was designed in such a way to come from the definition of creative economy while eliminate discrepancies of previous models. Findings: The current outputs have shown that regions with a significant creative potential (expressed by the New creative index) are achieving higher rate of economic level, more favorable demographic structure, better results in employment and in others macroeconomic indicators. Conclusions: The understanding of the concept of creative economy is the first step for setting strategy that will lead to ensuring competitiveness in today‘s global world.
The Origin of the Creative Economy Including the Demonstration of the Impact on Economic Development
Keywords: creative economy; New creative index; Richard Florida; creativity; creative regions; competitiveness